A redescription of Harpactea dufouri (Thorell, 1873) (Araneae, Dysderidae), its occurrence outside the Balearic Islands, and some notes on the corticalis group of the genus - Bosselaers, Jan; Van Keer, Johan (European Journal of Taxonomy, 2016)
Harpactea dufouri (Thorell, 1873) was collected in the Gavarres protected natural area in Catalonia, Spain. The specimens were compared with specimens from Mallorca, Balearic Islands, and found to be conspecific. The female of the species is described here for the first time. The new finding proves that Harpactea dufouri occurs outside the Balearic Islands. The species, however, may be endemic to Catalonia.